Exposure to particulate matter on an Indian stone-crushing site. Issue 5 (6th August 2007) - Semple, S; Green, D A; McAlpine, G; Cowie, H; Seaton, A
Abstract : Background/objectives: A large number of labourers work in the stone-crushing industry in India. Many of these workers are also exposed to high levels of particulate matter in their homes from the use of biomass fuels. As part of our investigations to examine the health of these workers we characterised their exposure to respirable crystalline silica and a number of other particulate matter exposure metrics in both occupational and domestic settings. Methods: We used a combination of direct reading and gravimetric sampling of respirable dust, total inhalable dust and particulate matter <2.5 μm in diameter (PM2.5 ) at work (n = 19), within the general environment (n = 6) and inside the home (n = 7). We used x-ray diffraction to quantify the level of crystalline silica in the respirable dust samples. Results: After correcting for the length of the working week, the arithmetic mean 8-hour time-weighted average (TWA) total inhalable dust exposure for this group was 143 mg/m 3, the mean 8-hour TWA respirable dust exposure was 39.7 mg/m 3 and the 8-hour TWA crystalline silica exposure was 2.29 mg/m 3 . Our real-time data showed peaks in exposure under certain environmental and/or working conditions. General environmental and domestic PM2.5 exposures were also high. Conclusions: Particulate matter exposures experienced by this group of workers and their families are likely to produce impaired lung function within a short time-frame. There is a need to introduce simple measures to reduce particulate matter exposure from both occupational sources and the use of biomass fuels in homes on this and similar sites.